GOVERNMENT AND PRIVATE COLLABORATION: AN EFFORT TO STRENGTHEN INNOVATION SMALL SCALE FARMERS IN INDONESIA - Gema Wibawa Mukti; Rani Andriani Budi Kusumo; Anne Charina (Universitas Galuh, 2023)
Agriculture globally is still dominated by small-scale farmers which means that investment is still needed to change their quality of life for the better. Investment in innovation in agriculture is expected to not only alleviate poverty, but also improve the welfare of farmers and rural communities. To create this, collaboration between agricultural actors is needed, so as to encourage actors to play roles according to their respective functions, strengthening each other so that in aggregate it can increase farmers' productivity. Productivity growth, agricultural efficiency and reducing the impact of agriculture on the environment arise due to various studies conducted on the agricultural sector. Rural poor still rely on agriculture as their main livelihood, therefore investment in agriculture is an important factor in efforts to reduce poverty in rural areas, namely by improving agricultural performance. Collaboration between the government and the private sector is expected to improve soft skills and hard skills from each party, so as to improve services to agricultural stakeholders optimally. The government and agricultural stakeholders always collaborate with each other to encourage agricultural ecosystems that are able to overcome food insecurity and create sustainable agriculture. With the right model of iolaborasi, science-based innovation can encourage the strengthening of the agricultural industry and increase the level of welfare of smallholder farmers in rural areas.